TAMSULOSIN OR SOLIFENACIN IN LUTS PATIENTS DUE TO DJ-STENT INSERTION - Subkhan, Subkhan; Djojodimedjo, Tarmono; Hakim, Lukman; Budiono, Budiono (Indonesian Urological Association, 2013)
Objective: To evaluate the efficacy of tamsulosin or solifenacin for treatment of Lower Urinary Tract Symptoms (LUTS) due to an indwelling ureteral stent. Material & Method: In this study, we enrolled 24 patients who had polyurethane DJ-stent inserted for urinary stone disease or ureteral stenosis. Patients were divided into 3 equal groups as follows and study medications were started on postoperative day 7. Group I received tamsulosin 0,4 mg once daily, group II received solifenacin 5 mg once daily, and group III only received placebo. LUTS were evaluated using International Prostatic Symptoms Score (IPSS) questionnaire at 7 and 14 days after the procedure and stent insertion. The evaluation of IPSS score included not only total score but also irritative and obstructive subcores. Results: All 24 patients fulfilled the inclusion and exclusion criteria, mean age of tamsulosin group was 54,3 years old, solifenacin group was 45,3 years old and placebo was 46,7 years old. There was significant difference in the total IPSS and irritative subscores between groups who received either tamsulosin or solifenacin (group I and II), whereas the obstructive subscore showed a difference though not statistically significant. Conclusion: Tamsulosin or solifenacin significantly improved irritative symptoms of LUTS in patients with an indwelling ureteral stent.Keywords: Lower urinary tract symptoms, DJ-stent, tamsulosin, solifenacin.